PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING UNTUK MENGAKTIFKAN BELAJAR SISWA PADA MATA PELAJARAN PPKN DI SMA NEGERI 1 SIPISPIS KEC.SIPISPIS KAB.SERDANG BEDAGAI - Evi Santi; Ulian Barus (Jurnal Inovasi Penelitian, 2022)
The formulation of the research problem is whether the application of the student facilitator and explaining learning model can activate the learning of Civics students in the class of SMA Negeri 1 Sipispis. This type of research is Classroom Action Research (CAR) which consists of four stages, namely planning (planning), action (acting), observation (observing), and reflection (reflecting). The research subjects were students of class XI IPS 1 of SMA Negeri 1 Sipispis totaling 30 students consisting of 18 female students and 12 male students. To obtain this field data, the author uses data collection techniques in the form of observation sheets and tests. The data analysis technique was carried out after the data was obtained from the test results by calculating the level of student learning activity and calculating student learning completeness. Based on the results of the study, it was found that learning activities using the Student Facilitator and Explaining learning model obtained an average result of learning activities in the first cycle of 43.7 with sufficient criteria and in the second cycle the average student activity was 75 with good criteria. Based on data analysis on student learning outcomes, in the first cycle obtained an average of 46.6% with less criteria. In Cycle II, student learning outcomes increased with an average score of 80 with good criteria. Thus, it can be concluded that there is an increase in teacher activity and student learning activities in class XI IPS 1 SMA Negeri 1 Sipispis by using the Student Facilitator and Explaining learning model.